COMPREHENSIVE ANALYSIS OF CITIZENS: CONCEPT, LEGAL STATUS, DETERMINATION MECHANISMS, AND THE STATUS OF INDONESIAN CITIZENS WITHIN THE INDONESIAN CONSTITUTIONAL SYSTEM - Bambang Yuniarto; Haura Zanatul Ma'wa; Ahmad Alviansyah; Muhamad Ilham Badar; Rahma Fadilah; Rindi Fatmawati (CV. ADIBA AISHA AMIRA, 2025)
This research aims to comprehensively analyze the concept of a citizen, the position of citizens within the state governance system, the mechanisms for determining citizenship, and the status of Indonesian Citizens (WNI) based on the national legal framework. The issues examined include how the definition of a citizen is formulated in citizenship theory and the constitution, how the constitutional position of Indonesian Citizens is regulated in the 1945 Constitution, and how the mechanisms for acquiring, losing, and restoring citizenship are established through Law No. 12 of 2006 and its implementing regulations. This research employs a qualitative method with a descriptive-analytical approach through a literature study, utilizing data sources such as constitutional documents, citizenship laws, Constitutional Court rulings, national and international academic literature, and previous relevant research. The results indicate that Indonesia's citizenship system is constitutional, legal, and oriented towards protecting citizens through systematic and adaptive regulations concerning rights, obligations, and citizenship administration procedures. The findings also reveal that contemporary issues such as limited dual citizenship, mixed marriages, global migration, and the existence of the Indonesian diaspora demand enhanced citizenship literacy and regulatory refinements to be more responsive to modern socio-political changes. Overall, this research provides theoretical and practical contributions to strengthening citizenship education, fostering national character, and developing more inclusive and equitable public policies regarding the status, protection, and participation of citizens within the Indonesian constitutional system.